The effect of the hands-on activity learning model assisted by the opportunity board on students' mathematical representation ability - Sri Winarsih; Nurul Husnah Mustika Sari (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Mathematical representation ability is a crucial skill in mathematics learning; however, many students still struggle to express mathematical ideas in various forms of representation. One contributing factor is the learning model that does not sufficiently support the concrete exploration of concepts. This study aims to examine the effect of the Hands-On Activity model assisted by the Opportunity Board on students' mathematical representation abilities. The research method employed was an experimental approach with a Quasi-Experimental design. The study population consisted of 170 students, with a purposive sampling technique used to select 64 students, who were then divided into experimental and control groups. Data were collected through a pretest and posttest and analyzed using an independent samples t-test. The findings revealed that the experimental group showed a significantly greater improvement compared to the control group. The mean posttest score of students in the experimental class was higher, with a t-value of 4.882, exceeding the t-table value of 1.998 at 62 degrees of freedom (df). Additionally, the p-value = 0.001 was lower than the 0.05 significance level, leading to the rejection of H₀ and acceptance of H₁. These results indicate that the HOA model assisted by the Opportunity Board is effective in enhancing students' mathematical representation abilities. This study is expected to provide valuable insights for educators in implementing more interactive and experience-based learning methods to optimize students' mathematical understanding.